Narratives and counter-narratives in pharmaceutical patent law making : experiences from 3 developing countries. - Vanni, Nneamaka (2016)
This empirical thesis explores the ways some Third World States use the patent regime as set out in the TRIPS Agreement to effect certain development and public health goals. It also investigates how non-state actors in these countries participate in patent law making, thereby creating narratives and counter-narratives that are challenging global norms on pharmaceutical patent protection. To do this, the thesis takes the three different examples of Brazil, India, and Nigeria and tells the story of patent law making within each of them. Adopting a Third World Approach to International Law as a macro-theoretical guide and nodal governance theory as a supplement, the thesis maps the broad interpretations and contestations of international patent law within the Third World. In doing this, the thesis pays particular attention to the everyday life of international patent law through the examination of practices that unfold through the different sites and objects in which international law operates today. In unpacking the patent law making in the aforementioned countries, the thesis posits that there is an emerging body of IP jurisprudence from the Third World that is expanding the aperture on norms governing pharmaceutical patent rules and medicines access discourse. In other words, the politics of international law making and implementation is shifting dramatically due to the confluence of different actors from various sectors in different forums in Brazil and India that are articulating counter-hegemonic pharmaceutical patent rules. The concomitant effect is not only the adoption of alternative pharmaceutical patent laws that are pro-human rights – especially pro-public health rights – in its articulation, but are also hermeneutic expressions of resistance against, and reform of, the international IP regime. In interrogating these narratives and counter-narratives that frame the global intellectual property regime in Third World forums, this thesis articulates successful counter-hegemonic discourses on patent law making and extrapolates lessons for Nigeria.